Efficiency and Equity of educational systems in the light of prescribed curriculum within a competency-based approach. The case of the French speaking Community of Belgium - Demeuse, Marc; Duroisin, Natacha; Soetewey, Sabine; Derobertmasure, Antoine (Swiss Journal of Educational Research, 2018)
Besides research concerning the efficiency and the equity of education systems through comparisons of international statistics or the study of pupils’ flows within education systems, it is possible to take into account these two main dimensions through the analysis of curricular material. This is what this article provides with in a very particular context: the French-speaking Belgium school community where curricula, although prescribed within a framework of common rules and references, allow a large degree of freedom to education networks. The main thesis developed here suggests that this freedom is probably not a factor of efficiency and equity in an educational system still weakly regulated.